Outcomes of a Multicenter Training Program in Laparoscopic Pancreatoduodenectomy (LAELAPS-2). Issue 2 (February 2019) - de Rooij, Thijs; van Hilst, Jony; Topal, Baki; Bosscha, Koop; Brinkman, David J.; Gerhards, Michael F.; de Hingh, Ignace H.; Karsten, Tom M.; Lips, Daan J.; Luyer, Misha D.; Marsman, Hendrik A.; van Rijssen, L. Bengt; et al.
Abstract : Objective: The aim of the study was to assess feasibility and outcomes of a multicenter training program in laparoscopic pancreatoduodenectomy (LPD). Background: Whereas expert centers have reported promising outcomes of LPD, nationwide analyses have raised concerns on its safety, especially during the learning curve. Multicenter, structured LPD training programs reporting outcomes including the first procedures are lacking. No LPD had been performed in the Netherlands before this study. Methods: During 2014–2016, 8 surgeons from 4 high-volume centers completed the Longitudinal Assessment and Realization of Laparoscopic Pancreatic Surgery (LAELAPS-2) training program in LPD, including detailed technique description, video training, and proctoring. In all centers, LPD was performed by 2 surgeons with extensive experience in pancreatic and laparoscopic surgery. Outcomes of all LPDs were prospectively collected. Results: In total, 114 patients underwent LPD. Median pancreatic duct diameter was 3 mm [interquartile range (IQR = 2–4)] and pancreatic texture was soft in 74% of patients. The conversion rate was 11% (n = 12), median blood loss 350 mL (IQR = 200–700), and operative time 375 minutes (IQR = 320–431). Grade B/C postoperative pancreatic fistula occurred in 34% of patients, requiring catheter drainage in 22% and re-operation in 2%. A Clavien-Dindo grade ≥ III complication occurred in 43% of patients. Median length of hospital stay was 15 days (IQR = 9–25). Overall, 30-day and 90-day mortality were both 3.5%. Outcomes were similar for the first and second part of procedures. Conclusions: This LPD training program was feasible and ensured acceptable outcomes during the learning curve in all centers. Future studies should determine whether such a training program is applicable in other settings and assess the added value of LPD.